Modified RS‐LAMP assay and use of lateral flow devices for rapid detection of Leifsonia xyli subsp. xyli. (1st December 2017) - Naidoo, N.; Ghai, M.; Moodley, K.; Mkize, L.; Martin, L.; McFarlane, S.; Rutherford, S.
Abstract: Ratoon stunt (RS) caused by bacterium Leifsonia xyli subsp. xyli ( Lxx ) results in substantial yield losses in sugarcane ( Saccharum sp. L. hybrid). Since RS does not produce reliable symptoms in the field, laboratory‐based techniques are necessary for detection. Loop‐mediated isothermal amplification (LAMP) assay overcomes the limitations of laboratory‐based techniques which are costly, time consuming and cannot be used for near‐field detection. A sensitive LAMP assay was developed to detect Lxx at 65°C in 30 min. However, carry‐over contamination affected the reliability of the assay. In the present study, contaminants were successfully eliminated by incorporation of uracil nucleoside glycosylase (1 U μ l −1 ) into the LAMP assay and incubation for 10 min at 37°C. To avoid the use of colorimetric reagents, lateral flow devices were successfully used for the detection of LAMP products and were equally sensitive to detection by agarose gel electrophoresis. The use of exudate from leaf sheath discs as an alternate template for the LAMP assay was found to be less sensitive than xylem sap. The preprepared master mix could be stored for up to 4 months at −20°C without any reduction in performance. These changes make the assay suitable for near‐field detection in laboratories with basic facilities. Significance and Impact of the Study: This study presents a modified loop‐mediated isothermal amplification (LAMP) assay for the detection of Leifsonia xyli subsp. xyli . Modifications include incorporation of uracil nucleoside glycosylase to eliminate carry‐over contamination and substitution of colorimetric detection for the use of lateral flow devices. LAMP master mix was preprepared and was stably stored up to 4 months at −20°C. Sugarcane leaf sheaths worked well as a substitute to xylem sap as template, although the sensitivity was lower. These modifications allow the assay to be conducted without contamination concerns and reduction in set up time, making it ideal for near‐field diagnosis.